Relationship Between Gender of the Consumer and Service Quality in Context of Life Insurance Policy in India - Bhatia, Deepak (Journal of Commerce and Trade, 2021)
The significant research areas that can be seen were studying the dimensions of service quality and designing measuring scales for diverse service industries. In a few cases, the impact of organizational characteristics on service quality has also been investigated. Particularly in India's Life Insurance Company (LIC). However, relatively few research in the domain of service quality have been conducted in Meerut. The study mainly focuses only on the retail consumer of 2 years of the Life Insurance Companies with in the local context. And also, the researches evaluate how the level of service quality varies in terms of the gender of the consumers. This study examines the relationship between service quality aspects and perceived service quality, taking into account customer gender variations, in order to explain actual conditions rather than explore cause and effect scenarios. The findings show that banks should provide a greater degree of service to their customers regardless of the gender of the customer, implying that it is difficult to satisfy customers nowadays because their expectations are higher. In any case, the amount of income does not play a large role in market segmentation by insurance companies, and so is not a good demographic feature to segment the markets. Both primary and secondary data were used to gather required data. Primary data was gathered using the survey approach, using a structured questionnaire constructed using the SERVQUAL Model, and variables were operationalized using the SERVQUAL instrument. Classification-JEL : L36